Implementation of the Indonesia Pintar (PIP) Program Policy at the Syekh Abdul Halim Hasan Institute in Binjai - Lubis, Muhammad Haekal; Lubis, Maksum Syahri; Batubara, Beby Masitho (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the implementation of the Indonesia Pintar Program (PIP) at the Syekh Abdul Halim Hasan Institute in Binjai City. The focus of the study is on policy implementation and factors that hinder the program. The approach used is descriptive qualitative research with data collection techniques through observation, in-depth interviews, and documentation. Research informants included the Vice Rector III, the Head of Academic Affairs, and PIP recipient students. The results of the study show that the implementation of the Indonesia Pintar Program at the Syekh Abdul Halim Hasan Institute in Binjai City has been running quite well in accordance with the guidelines of the Ministry of Religious Affairs. However, the implementation of this policy still faces obstacles in terms of socialization, delays in fund disbursement, and limitations in human resources and supporting technological facilities. Communication and coordination between institutions are crucial aspects that need to be improved. The PIP program has proven to help students from underprivileged families, but its effectiveness can still be improved through evaluation, service digitalization, and transparency of recipient data.